Study of Ion-Isotopic Self-Diffusion Reactions as a Function of Ionic Concentration and Temperature - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2016)
Radioactive isotope 82Br has been used as a tracer to study the kinetics of ion-isotopic self-diffusion reactions. The study was carried out in the temperature range of 27.0-48.0 °C using 0.010 M labeled bromide ion solution and 1.0 g of ion exchange resins in bromide from, to study the temperature effect on kinetics of self-diffusion reaction was studied in the concentration range of 0.005-0.100 M labeled bromide ion solution, using 1.0 g of ion exchange resins in bromide form and at a constant temperature of 32 ºC.